Identification of plasmalogens in Bifidobacterium longum, but not in Bifidobacterium animalis - Mawatari, Shiro (Sci Rep, 2020)
Plasmalogens are glycerophospholipids that contain a vinyl ether bond at the sn-1 position of glycerol backbone instead of an ester bond. Plasmalogens are indicated to have many important functions in mammalian cells. On the other hand, it is suggested that some gut microbiota plays many probiotic functions to human health. Presence of plasmalogens in Clostridium strains in gut microbiota is well-known, but presence of plasmalogens in Bifidobacterium longum (B. longum) strain, one of the most important probiotic gut microbiota, has not been reported. We identified plasmalogens in lipid extract from some B. longum species, but not from Bifidobacterium animalis (B. animalis) species which are another important strain of probiotic bifidobacteria. Major phospholipid classes of plasmalogens in B. longum species were cardiolipin, phosphatidylglycerol and phosphatidic acid. Almost all of the phospholipids from B. longum examined were indicated to be plasmalogens. Although major phospholipid classes of plasmalogens in human brain and major phospholipid classes of plasmalogens in B. longum are different, it is interesting to note that many reported functions of microbiota-gut-brain axis on human neurodegenerative diseases and those functions of plasmalogens on neurodegenerative diseases are overlapped. The presence of plasmalogens in B. longum species may play important roles for many probiotic effects of B. longum to human health.